Sustainability of Pesantren In The Future: Study of Charismatic Leadership of Kiai and Leadership Succession of Pesantren in Pekalongan - Ahmad Ta'rifin; Ahmad Halid (Edukasia Islamika, 2021)
This study aims to reveal the impact of the charismatic leadership of six (6) pesantren’s kiai and their leadership succession on the sustainability of the pesantren in the future. The research method uses historical and phenomenological approaches. This research reveals the fact that the pesantren that still exist and continue today are due to the charismatic leadership of the kiai accompanied by the institutional development of the pesantren. Likewise, the succession of pesantren leadership is carried out through good regeneration. On the other hand, the pesantren which were "destroyed" after the kiai's founders died, was due to the charismatic leadership of kiai not being accompanied by the formalization of the pesantren by developing formal educational institutions or other institutions under the pesantren, and the succession of pesantren leadership was not accompanied by structured regeneration.